Bioecology and Integrated Management of Banana Pseudostem weevil Odoiporus Longicollis Oliv - Anitha N (Department of Agricultural Entomology, College of Agriculture, 2000)
A study on bioecology and integrated management of banana pseudostem weevil Odoiporus longicollis Oliv. Was carried out by various laboratory and field experiments at the Department of Agricultural Entomology, College of Agriculture, Vellayani, Thiruvananthapuram during 1996-2000.